2011
DOI: 10.1063/1.3591883
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Piezoelectric Stack Actuators for Vibrothermography

Abstract: Vibrothermography, also known as Sonic IR and thermosonics, is an NDE technique for finding cracks and flaws based on vibration-induced frictional rubbing of unbonded surfaces. The vibration is usually generated by a piezoelectric stack actuator which transduces electrical energy into large amplitude mechanical vibrations. The amplitude and impedance transfer characteristics of the transducer system control the vibration of the sample. Within a linear contact (no tip chatter) model, the interaction between the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Similarly, Rizi et al [5] used the same finite element analysis procedure to qualitatively study the heating mechanisms in defected areas. A few authors such as Vaddi et al [17] studied the effect of adding ultrasonic piezoelectric stack actuators in the vibrothermographic excitation system. However, there are not yet any studies which couple the electrical model of ultrasonic transducers into the thermomechanical model of the specimen under inspection in order to form a more comprehensive and realistic thermo-electromechanical model.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Rizi et al [5] used the same finite element analysis procedure to qualitatively study the heating mechanisms in defected areas. A few authors such as Vaddi et al [17] studied the effect of adding ultrasonic piezoelectric stack actuators in the vibrothermographic excitation system. However, there are not yet any studies which couple the electrical model of ultrasonic transducers into the thermomechanical model of the specimen under inspection in order to form a more comprehensive and realistic thermo-electromechanical model.…”
Section: Introductionmentioning
confidence: 99%
“…Han et al [21] experimentally verified the effectiveness of VT for turbine blade crack detection and found the enhancement of crack detectability by acoustic chaos. Holland et al [22,23] quantitatively evaluated the performance of piezoelectric stack actuators in a VT excitation system and investigated the effect of actuator performance and specimen characteristics on the excitation effect. Zhang et al [24] confirmed the impact of engagement force on crack frictional heating by an ultrasonic gun with a maximum power of 1.25 kW.…”
Section: Introductionmentioning
confidence: 99%
“…A broadband excitation system was used to generate vibrations at the desired frequencies in the specimen [Vaddi (2011)]. A layer of cardstock material was used as a couplant between transducer tip and the specimen to eliminate transducer-specimen combined system resonances [Vaddi et al (2011)]. A laser vibrometer measured the specimen vibrations while a calibrated infrared camera was used to measure the temperature rise in the coating.…”
Section: Methodsmentioning
confidence: 99%
“…The use of cardstock or a similar compliant material between transducer and specimen breaks specimen-transducer system resonances [Vaddi et al (2011)]. It also reduces nonlinearity and the potential for unpredictable "chaos" at the tip-specimen contact.…”
Section: Transducer Consistency and Modelingmentioning
confidence: 99%